Fluorescence of molecules placed near a spherical particle: Rabi splitting - Dvoynenko, M.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Theoretical study of spontaneously emitted spectra of a point-like source placed near a spherical Ag particle was performed. It was shown that near-field electromagnetic interaction between a point-like emitter and a spherical Ag particle leads to strong coupling between them at very small emitter-metal surface distances. It was shown that the values of Rabi splitting are quantitatively close to those of emitter-flat substrate interaction.